Pengaruh Pendidikan Kesehatan Asupan Cairan terhadap Kepatuhan Pembatasan Cairan Pasien Hemodialisis - Riswahyuni Widhawati; Fitriani Fitriani (Faletehan Health Journal, 2021)
Patients with Chronic Kidney Disease (CKD) undergoing a regular hemodialysis twice a week or three times a week tend to experience an excessive fluid volume due to the decreased kidney function. An excessive fluid intake is one of causes of death in CKD patients. The study aims to examine the influence of health education on the adherence to fluid intake restriction among hemodialysis patients at Ichsan Medical Centre (IMC) Hospital in Bintaro, South Tangerang. This research used quantitative approach with quasi-experimental method and pretest and posttest non-equivalent control group design. The research sample consisted of 40 hemodialysis patients (20 experimental patients and 20 control patients). The intervention got by the experimental group was health education of fluid intake restriction. The data collection used questionnaire. The analysis used univariate and bivariate with paired sample T test and independent T test. The results of data analysis showed that there was influence of providing health education on the experimental group (p = 0.000), yet there was no difference of adherence to fluid restriction (p = 0.330) in the control group who got no health education. The researchers concluded that there is an influence of health education provision on the level of adherence to fluid restriction in CKD patients.